Flebotomíneos (diptera: psychodidae) em áreas de ocorrência de leishmaniose na região sudeste do Brasil - Santos, Jennifer Diniz dos (2019)
Insects belonging to the order Diptera, family Psychodidae and subfamily Phebotominae, popularly known as mosquito straw or birigui, are considered vectors of leishmaniasis. Leishmaniasis is a complex of infectious diseases caused by protozoa of the genus Leishmania spp., Characterized as neglected zoonoses of major public health importance. In this context, and due to the increase in the number of leishmaniasis cases, the objective of this study was to investigate the phlebotomine fauna in three municipalities of the northeast region of São Paulo (Rifaina, Franca and Pedregulho) and in Delfinópolis-Minas Gerais. The entomological captures were performed during five consecutive nights in each municipality, from April to July 2019. As criterion for selection of strategic points, neighborhoods or regions with incidence of canine leishmaniasis cases, notified by health surveillance in the evaluated municipalities, were selected. After collection, the insects were analyzed for the presence of sand flies, followed by municipalities of Franca, Pedregulho, Rifaina and Delfinópolis respectively. In the four studied areas, there was variation in the phlebotomine fauna and were identified the total of 17 species, belonging to the subfamily Phebotominae, Subtribos Psychodopygina Brumptomyiina, Sergentomyiina, Lutzomyiina. Among the identified species, three are related to the transmission cycle of cutaneous and visceral Leshimaniasis, namely Nyssomyia whitmani, Migonemyia (Migonemyia) migonei and Lutzomyia (Lutzomyia) longipalpis, the latter reported for the first time scientifically in the region. Thus, it is concluded that the survey of species in each region can clarify important points in understanding the transmission of the disease and strengthen public health policies in specific areas of presence of sandflies.